Managing Water : Avoiding Crisis in California - Green, Dorothy, 1929-2008 (Book collections on Project MUSE., 2007)
Water in California is controlled, stored, delivered, and managed within a complex network of interlocking and cooperating districts and agencies. Unraveling and understanding this system is not easy. This book describes how the system works and discusses the issues that face elected officials, water and resource managers, and the general public.